Abandoned Mine Reclamation and Principal Considerations on Utilization - Siriluck, Siwarote; Chuenjai , Pipatt (RMUTL Engineering Journal, 2023)
The utilization has been presented for the seven abandoned mines as the successful projects. The development and maintenance expenditure have been used for the safety mine place throughout the time by the business owners. The projects are the Salina turda amusement park, Wieliczka underground church, the glow radioactive scuba diving, the underground mine ATV riding resort, the dirt racetracks, the Eden project and the intercontinental Shanghai wonderland hotel. The article objective is to provide the guidance of a business development for the abandoned mine location in the future. A subsequent section has established the guidelines for the utilization from abandoned mine which related with the geological information, the constraints of mine design and mine environment conditions. The seventeen principles are the types of mines, a mine owner, the present actual conditions, a route access, a location, a description of mapping surface-underground area, a geological deformation, the geotechnical risks with abandoned mining, a support of the expanded area, the water flow direction and the seasonal flooding area, a wind map, a sewage map, an interactive underground water map, the vibration level, the noise level and the biodiversity. The final section is the analytical guidelines of the domestic abandoned mines utilization. It is hoped that to future this principles can be better developed and it will be a suitable guidelines for the local abandoned mines.